Seasonal energy storage for district heating applications, including simulation and analysis of Borehole Thermal Energy Storage systems - Bakken, Nils Joakim Døvre (UiT The Arctic University of Norway, 2018)
The objective of this thesis is to analyse different energy storage technologies for seasonal energy storage in combination with district heating. Tromsø receives district heating (Kvitebjørn Varme). Their new heating central at Skattøra burn waste from industry and households in Tromsø and this heat is used to heat water. A part of this excess heat is lost to air during summer because of a lower energy demand in summer than in winter, and this work look into the possibility to store this excess heat from summer for use in winter when the demand is higher. A storage could cover peak demands during winter instead of burning oil. The study looks into ATES systems which stores thermal energy in aquifers in the ground, CTES systems which stores energy as hot water in large underground caverns and BTES systems which exchanges heat with the ground with vertical borehole heat exchangers through a circulating fluid. It also analyse energy storage in PCMs (Phase Change Materials) and chemical storage which stores energy in chemical reactions. After analysing the different storage technologies, BTES systems shows to be the most economical and most practical alternative for Kvitebjørn. The second part of this thesis uses a simulation program called Earth Energy Designer (EED) to analyse BTES systems of different sizes and with different heat loads. Based on a set of input parameters, EED calculates the mean fluid temperature in the circulating fluid which flows through the boreholes. Because of uncertainties of the amount of excess heat and monthly distribution of this heat, I do many simulations with different heat loads and monthly profiles. Borehole configurations for a limited area where a BTES system for Kvitebjørn could be placed is also analysed. Since thermal response tests have not been taken in the area, I do a sensitivity analysis to see how variations in ground parameters influence on the results. I also look at the possibility of preheating the storage for some years. Finally, I look into project costs and ...